Re-assessment of depositional conditions of Cretaceous deposits around the Amfilochia and Arta areas - Dimopoulos, Nikolaos; Georgoulas, Eleftherios; Peridis, Savvas; Iliopoulos, George; Bourli, Nicolina; Antoniou, Panayiota; Zelilidis, Avraam (Bulletin of the Geological Society of Greece, 2019)
Sedimentological studies of the Cretaceous limestones in the central Ionian basin (Amfilochia, Arta as well as Kerasonas areas) indicate that these deposits are composed of calciturbidites interbedded with breccia-microbreccia deposits. In the Amfilochia new cross-section, with a NNW-SSE direction, the lower Cretaceous Vigla limestones and Vigla shales were outcropped for the first time. This section is directed parallel to the paleo Ionian basin axis and the fact of the lateral discontinuity of Vigla limestones and Vigla shales indicate that during the sedimentation of these two Formations there was a restriction along the paleo basin axis, probably due to synsedimentary transfer fault activity. Forty-two (42) samples from Vigla shales were analyzed for their content in CaCO3 and TOC, showed that these sediments present poor to fair hydrocarbon potential. In the Arta new cross-section, with a NE-SW direction, the Upper Cretaceous Senonian deposits showed strong deformation that took place during the compressional regime that affected the Ionian basin after sedimentation. This deformation appears stronger in the western part being close to a major thrust, and thus it is possible that this deformation could be responsible for the high secondary porosity of Upper Cretaceous deposits. Microfacies analysis of these deposits showed in general that deep-sea depositional environments prevailed, nevertheless in a few cases indications for the presence of environments with a shallow character imply the existence of isolated carbonate platforms close to the studied sections. In the studied sections with an E-W direction, no lateral changes were observed in the depositional conditions within the same Formation introducing standard depositional conditions across the paleo basin.